2010
DOI: 10.2522/ptj.20090158
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Clinical Scale to Stratify Risk of Recurrent Falls in Community-Dwelling Adults Aged 65 Years and Older

Abstract: Clinicians could easily classify older patients in low-, moderate-, or high-risk groups of recurrent falls by using 4 easy-to-obtain items. The Five-Times-Sit-to-Stand Test provides added value to stratify risk for falls in people at moderate risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 33 publications
7
120
0
4
Order By: Relevance
“…The mechanical load may lead to bone strengthening with mobility-induced weight-bearing stress [3]. Thus, our results are in accordance to previous studies that demonstrated that weight loss may increase the bone turnover, suggesting that body weight enhances the differentiation of osteoblasts and increase osteoblastic bone formation besides attenuates osteoclastic activity [13,14,15,18].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The mechanical load may lead to bone strengthening with mobility-induced weight-bearing stress [3]. Thus, our results are in accordance to previous studies that demonstrated that weight loss may increase the bone turnover, suggesting that body weight enhances the differentiation of osteoblasts and increase osteoblastic bone formation besides attenuates osteoclastic activity [13,14,15,18].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, previous studies suggested that fat mass is associated with whole body BMD in older women, independent of lean mass [15]. The relationship between body composition and endocrine control is related to the production of peripheral gonadal hormones by adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tests used in this study are reliable and valid clinical tools commonly used in assessing muscle strength and mobility in community‐dwelling older adults. Moreover, they require limited space and can be administered quickly 8, 31, 32. Although these clinical tests are very simple, parameters with poor performance predict adverse health in older adults and would have advantages over other common markers.…”
Section: Discussionmentioning
confidence: 99%
“…Isso permite dizer que o uso prévio de medicamentos às quedas é um fator de risco também para fraturas. A medicação mais utilizada nos pacientes deste estudo que tiveram fratura foi também o anti-hipertensivo (Hamra, Ribeiro, Miguel, 2007 fortemente associado a quedas e pode prever a ocorrência das mesmas (Buatois et al, 2010;Bongue et al, 2011).…”
Section: Coleta De Dadosunclassified